Problem Solving through Teamwork Using Puzzle Media for 10 years old Children in Dukuhwaluh Village - Gisella Arnis Grafiyana; Intan Nur Rahmawati; Lutfi Septiana Widyastuti; Syavira Berliana Syaskia Dewi; Fanisa Dwi Oktaviana; Aprilia Dwi Ayomi; Gina Safitri Rachmatillah; Antin Rohmawati (Proceedings Series on Social Sciences & Humanities, 2021)
Problem solving is a process that has been implemented in order to obtain a solution to a problem that is carried out in stages. Teamwork is the ability of individuals to work together with others and aims for members to be able to participate in the team and understand their duties. This study aims to determine the ability to solve problems and teamwork (teamwork) in children aged 10 years using puzzles. This research is an experimental study with a quasi-experimental design: non-equivalent control group design. The participants in this study were 8 children aged 10 years consisting of 5 boys and 3 girls. The data collection in this study was the acquisition of time in the preparation of puzzles. The data that has been obtained is then analyzed using the t-test (t-test). The results of this study indicate that the experimental group has faster problem solving than the control group because of the learning outcomes of teamwork.